Validitas Instrumen Tes Berbasis Literasi Sains untuk Mengukur Keterampilan Berpikir Kritis Siswa SMA pada Materi Energi Terbarukan (IPF: Inovasi Pendidikan Fisika, 2023)
This research aims to describe the theoretical and empirical validity of critical thinking test instruments based on science literacy on renewable energy materials that have been developed. This research stage refers to the limited ADDIE model whose steps include Analysis, Design, and Development. Research data was obtained through expert assessment tests and instrument trials. The test instrument was developed by referring to critical thinking indicators according to Facione which are aligned with science literacy competence. Test instruments are arranged in the form of description questions totaling 15 questions. Theoretical validity is obtained using validation sheets by three validators. Empirical validity was obtained through instrument trials on 30 students. The results of theoretical validity in the domains of material, construction and language respectively of 100%, 95% and 100% with an overall average of 98% are categorized as very valid. Empirical validity containing the validity of question items, reliability, difficulty and discriminating power obtained results of 60% of 15 questions or 9 questions declared feasible.